Identifying of the influence of chamber temperature on the flexural properties of polyamide 12 fabricated by FDM/FFF 3D printing - Nguyen, Mai Tran Phong; Pham, Thi Hong Nga; Ho, Thi My Nu; Le, Duong (Eastern-European Journal of Enterprise Technologies, 2026)
The thermal environment of the printing chamber is an important factor in determining the quality and mechanical performance of semi-crystalline polymers produced by Fused Deposition Modelling (FDM/FFF), such as Polyamide 12 (PA12). Nevertheless, the impact of temperature in the building chamber on the flexural performance of PA12 parts is not yet clear. The aim of this study is to evaluate the flexural performance of FDM/FFF-printed PA12 as a function of the building chamber temperature and different thermal processing conditions. A Taguchi L25 orthogonal design was employed to investigate the influence of nozzle temperature, bed temperature and building chamber temperature on flexural stress, bending force, elastic modulus and signal-to-noise ratio. The results showed relatively stable mechanical performance under different thermal conditions. Flexural stress ranged from 49.58 to 53.23 MPa, bending force from 173.10 to 185.83 N, and elastic modulus from 1014.26 to 1119.49 MPa. Statistical analysis indicated that building chamber temperature was the most influential, followed by nozzle temperature while bed temperature had the least impact. The optimal processing conditions were obtained at a nozzle temperature of approximately 280°C, a bed temperature of 60–75°C, and a building chamber temperature of 65°C. The improved flexural performance can be ascribed to enhanced interlayer bonding, lower thermal gradients and more stable heat transfer in the entire printing chamber. The results emphasize the important role of chamber temperature at several critical stages during printing in improving structural integrity and mechanical reliability of FDM/FFF-printed PA12 components. The obtained results can be applied to the fabrication and optimization of PA12 engineering components produced under controlled thermal conditions